Seed vigor and germination of facheiro plants (Pilosocereus catingicola (Gurke) Byles & Rowley Subsp. salvadorensis (Werderm.) Zappi (Cactaceae) at different temperatures - De Medeiros, Robson Luis Silva [UNESP]; De Souza, Vênia Camelo; De Azerêdo, Gilvaneide Alves; Neto, Miguel Avelino Barbosa; Barbosa, Alex Da Silva; Oliveira, Ivan Sergio Da Silva (Universidade Estadual de Londrina, 2017)
Several species of endemic Cactaceae are found in northeastern Brazil, which are important plants to the local fauna and flora; nevertheless, there are only a few studies assessing the germination of this plant genus. Understanding the germination of species native to the Caatinga is essential to subsidize conservation actions for such ecosystem. The objective of this study was to investigate the influence of three localities and different temperatures on the vigor and germination of facheiro seeds. The experiment was conducted by evaluating seed vigor and germination in three distinct areas (Arara, Bananeiras, and Boa Vista) at different temperatures (20, 25, 30, 35, 40, and 20-30 °C). Quantitative data were submitted to polynomial regression analysis at 5% significance with four replicates of 50 seeds. In Arara, germination rates at 20 and 25 °C reached 96% and, at 30 °C, 86%. The temperatures of 25 and 30 °C presented the best germination speed index. For the three studied areas, the highest germination rates were recorded at a constant temperature of 25 °C and at the alternating temperature (20-30 °C). Yet the highest germination speed was reached at 30 °C. Based on its sexual propagation, the taxon in question is able to survive in environments with temperatures ranging from 20 to 30 °C, as seen in the studied habitats.
Keywords: Agreste of Paraíba state; Facheiro; Physiological potential